Pengaruh Pendidikan Kesehatan Metode Audiovisual dan Media Flipbook terhadap Tingkat Pengetahuan Bahaya Seks Bebas pada Remaja di MA Rahmatullah Tulungagung Kabupaten Bojonegoro - Fauziah , Fatma; Aris, Arifal; Suhariyati; Kurniawati , Isro’atin; Chasanah, Irfa’ul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Free sex not only causes pregnancy and abortion, but also increasing a high risk of HIV/AIDS and other sexually transmitted diseases. Knowledge of free sex is very essential for adolescents in minimizing the risk of having premarital sex. One solution to increase students’ knowledge about the dangers of sex is by providing health education through audiovisual method and flipbook media. The purpose of this study was to determine the effect of audiovisual method and flipbook media on the level of knowledge in adolescents about the dangers of free sex. This study used a pre-experimental design one group pre-posttest design. The sample of this study was 35 adolescents obtained by total sampling technique. The data were collected using a questionnaire on the dangers of free sex. The independent variable in this study was the effect of health education with audiovisual method and flipbook media, while the dependent variable was the level of knowledge of the dangers of free sex. The data were analyzed using the Wilcoxon statistical test (p = 0.05), and it was obtained p = value 0.000. The results showed that before being given education about the dangers of free sex, most respondents (71.4%) had a poor level of knowledge, but after being given education about the dangers of free sex, most respondents (71.4%) had a good level of knowledge. It can be concluded that there is an effect of audiovisual health education method and flipbook media on the level of knowledge of the dangers of free sex in adolescents. With this effort, it is hoped that the audiovisual method and flipbook media can be implemented in reducing free sex in the community and at school. Keywords: Knowledge, adolescents, free sex